SOSIALISASI PROGRAM BINCANG HUKUM TERHADAP PENINGKATAN KESADARAN LITERASI HUKUM MASYARAKAT DI MANDAILING NATAL - Fadlan Masykura Setiadi; Zulfikar; Jhon Tyson Pelawi; Ahmad Mafaid; Muhammad Danil; Sarmadan Pohan (LPPM STAI Muhammadiyah Probolinggo, 2025)
Legal literacy is a fundamental aspect in forming a society that is aware of the law and able to exercise rights and obligations in a balanced manner. Unfortunately, the level of legal literacy in the Mandailing Natal region is still relatively low, as seen from the lack of public understanding of actual legal issues, especially legal practices related to social and religious life during the month of Ramadan. This community service activity aims to improve community legal literacy through the Bincang Hukum program organized by the Nayottama Reswara Legal Aid Foundation. The activity was held on March 17, 2025 at Dilan Coffee, Panyabungan, Mandailing Natal, involving 23 participants from lecturers, legal practitioners, students, and the general public. Evaluation through pre-test and post-test showed a significant increase in participants' understanding of the legal material presented. In-depth interviews and observations showed that the interactive dialog method and contextual presentation of materials were able to encourage active community participation. These findings suggest that an educative approach based on public discussion can be an effective model in increasing community legal awareness. This program also contributes to strengthening the role of universities and legal aid institutions in legal literacy-based community empowerment.